Serum Interleukin-2 (IL-2) Levels in Untreated and Treated in Batak Tribe Patients with Schizophrenia - Julius Martin Siagian; Elmeida Effendy; Mustafa M. Amin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
To find out the difference of serum IL-2 levels between untreated and treated in the Batak tribe patients with schizophrenia and healthy control and also to find out the association between serum IL-2 levels with PANSS score in the Batak tribe patients with schizophrenia. This study was cross-sectional approach using a one-way ANOVA welch test and to find a correlation between serum IL-2 levels with PANSS score in the Batak tribe patients with schizophrenia which is conducted in Prof. Dr. M. Ildrem Psychiatric Hospital Medan and Dr. Pirngadi General Hospital Medan from September 2019-November 2019. Subjects of untreated were 55 subjects and treated in the Batak tribe patients with schizophrenia were 55 subjects and healthy control were 55 subjects. There were significant differences between these three groups using post hoc Games-Howell test on the value of p<0.001 and also been found there was a significant correlation between serum IL-2 levels with PANSS score in the Batak tribe patients with schizophrenia using the Pearson correlation test (r=0.599, p=0.001 and r=0.501, p=0.001). It was founded that there were significant differences between serum IL-2 levels in three groups and also founded there was a significant correlation between serum IL-2 levels with PANSS score in the Batak tribe patients with schizophrenia.